Education of Village Youth in The Use of Used Cooking Oil to Become Environmentally Friendly Candles in Kemiri Village - Setiawan, Risqi Firdaus; jaelani, Okta Syahdia; Agustini, Anggie Eka; Wicaksana, Muhamad Miko Nata (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Used cooking oil is a household waste often thrown away, which can damage the environment and endanger health. This community service activity was carried out in Kemiri Village to educate young people about using used cooking oil to make environmentally friendly aromatherapy candles. The method used was interactive discussion and direct presentation so that participants not only understood the theory but were also able to spread the candle-making independently. The activity results indicated that participants were highly enthusiastic and actively engaged in the discussion. In addition to increasing awareness of the value of waste management, this activity created chances for small businesses based on recycled goods to grow. We expect this education, which uses household waste, to inspire the village youth to be more environmentally conscious and creative. According to this abstract, the SDGs' contribution is as follows: Contribution to Sustainable Development Goals (SDGs):SDG 12 – Responsible Consumption and ProductionSDG 13 – Climate ActionSDG 8 – Decent Work and Economic GrowthSDG 4 – Quality Education